Biotic interactions recorded in shells of recent rhynchonelliform brachiopods from San Juan Island, USA - Rodrigues, Sabrina Coelho (Natl Shellfisheries Assoc, 2007)
Biotic interactions between brachiopods and spionid polychaete worms, collected around San Juan Islands (USA), were documented using observations from live-collected individuals and traces of bioerosion found in dead brachiopod shells. Specimens of Terebratalia tranversa (Sowerby), Terebratulina unguicula (Carpenter), Laqueus californianus (Koch), and Hemithiris psittacea (Gmelin) were collected from rocky and muddy substrates, from sites ranging from 14.7-93.3 m in depth. Out of 1,131 specimens, 91 shells showed traces of bioerosion represented by horizontal tubes. Tubes are U-shaped, straight or slightly curved, sometimes branched, with both tube openings communicating externally. on internal surfaces of infested shells, blisters are observed. All brachiopod species yielded tubes, except for H. psittacea. Tubes are significantly more frequent on live specimens, and occur preferentially on larger, ventral valves. This pattern suggests selectivity by the infester rather than a taphonomic bias. Given the mode of life of studied brachiopods (epifaunal, sessile, attached to the substrate, lying on dorsal valve), ventral valves of living specimens should offer the most advantageous location for suspension-feeding infesters. Frequent infestation of brachiopods by parasitic spionids is ecologically and commercially noteworthy because farmed molluscs are also commonly infested by parasitic polychaetes. In addition, brachiopod shells are among the most common marine macroscopic fossils found in the Phanerozoic fossil record. From a paleontological perspective, spionid-infested brachiopod shells may be a prime target for studying parasite-host interactions over evolutionary time scales.
Keywords: biotic interaction; commensalism; parasitism; bioerosion; rhynchonelliform brachiopods; spionid polychaetes; San Juan Islands